Combined strength and endurance exercise induced fatigue and recovery - Kilpelänaho, Eeva-Maria (2012)
Muscular fatigue is usually defined as the inability to maintain a given exercise intensity or adequate muscle force and therefore maximal isometric force, neural activation and fast force production capacity have often used determinants of acute fatigue. The purpose of the present study was to measure the acute effects of combined strength and endurance exercise on force production, muscle activation and work economy. In addition this study investigated the rate of recovery comparing the active and passive recovery models and the association of the initial fitness levels of subjects. 16 (27 ± 4 years old) male reservists performed combined strength (5x10x70%RM leg-press) and endurance (5x10 min marching) loading and following either active (5x10x30% leg press and 5x5min walking) or passive (seated) recovery. Bilateral maximal isometric force (MVC), force-time curve, muscle activation (EMG) and blood lactate were measured before and after the combined loading to determine the acute fatigue and recovery. In addition, work economy and heart rate were detected during the loading. The mean (± SD) magnitude of combined exercise induced loss in MVC was 14.2 ± 9.5 % (n=16) (p=0.001), and the force-time curve (n=16) shifted significantly (p<0.05-0.01) to the lower level. Significant decreases (p< 0.05 - p < 0.01) occured also in the EMG values, and the mean work economy (VO2/km/h) decreased by 11 ± 11 % (p=0.001) during the loading. The mean blood lactate increased (p=0.001) to 4.02 ± 1.89 mmol/l but recovered during the following hour after the test. MVC, EMG and HR recovered totally in both groups by the next morning. In addition, a significant (p<0.05) association between the VO2max of the subjects and the magnitude of force decrease was detected. The VO2max of the subjects also showed an association with the heart rate recovery. The present findings suggest that strenuous combined strength and endurance loading results in acute fatigue in the neuromuscular system leading not only to the decreased force production capacity of the muscles but also to a decrease in the muscle activation of the exercised muscles. The study also showed that the better the aerobic fitness level of the subjects the smaller was the neuromuscular fatigue and faster the physiological recovery rate. In addition, the results of the present study suggest that the active recovery might have beneficial effects on faster recovery of neuromuscular performance. Studying the acute performance decrements and recovery by simulating the physical demands of combined strength and endurance exercise may provide some valuable insight into the development of training programs for military and sport missions and for optimizing soldiers and athletes’ capacity for physical performance.